Nanofibers generated from nonclassical organogelators based on difluoroboron β-diketonate complexes to detect aliphatic primary amine vapors. Issue 34 (8th August 2016) - Zhai, Lu; Liu, Mingyang; Xue, Pengchong; Sun, Jingbo; Gong, Peng; Zhang, Zhenqi; Sun, Jiabao; Lu, Ran
Abstract : Narrow band gap nonclassical π-organogelators self-assembled into nanofibers for detecting primary amine vapors via the decomposition of difluoroboron β-diketonate complexes. Abstract : New D–A–D type difluoroboron β-diketonate complexes with terminal triphenylaminesABA, ABVA andAVBVA were synthesized. It was found that stable organogels could be gained fromABVA andAVBVA without traditional gelation groups in mixed solvents containing 1, 4-dioxane, and balanced π–π interactions were the driving forces for the gel formation. Interestingly, the organogels based onABVA andAVBVA exhibited emission close to the NIR (near infrared) region. To the best of our knowledge, such narrow band gap low molecular-weight π-gelators have not been reported. In particular, xerogel-based films generated fromABVA andAVBVA could be used as sensors to detect gaseous aliphatic primary amines with high performance. For example, after exposing to saturated n -butylamine and n -propylamine vapors for 30 s, the emission of the films was quenched completely and new strong emission at ca. 560 nm appeared on account of the decomposition of the difluoroboron β-diketonate complexes.